2022
DOI: 10.1093/rheumatology/keac190
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of sequential biologic and targeted disease modifying anti-rheumatic drugs for rheumatoid arthritis

Abstract: Objectives Whether patients with rheumatoid arthritis (RA) benefit from repeated trials of biologic or targeted synthetic DMARDs (b/tsDMARDs) after three or more attempts is unknown. We aimed to describe treatment outcomes in each line of b/tsDMARD therapy. Methods Using data from the British Society for Rheumatology Biologics Register for RA from 2001 to 2020, change to a new b/tsDMARD (except biosimilar switches) was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Similarly, a review of multiple use of HCDs from the BSR biologics registry (Zhao et al, 2022) showed maintenance of response rates from fourth to sixth choices. However, the survey of HCD prescribers revealed that they were more pessimistic about the likelihood of response which highlights the importance of collecting systematic follow-up data.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, a review of multiple use of HCDs from the BSR biologics registry (Zhao et al, 2022) showed maintenance of response rates from fourth to sixth choices. However, the survey of HCD prescribers revealed that they were more pessimistic about the likelihood of response which highlights the importance of collecting systematic follow-up data.…”
Section: Discussionmentioning
confidence: 94%
“…The trend of decreasing therapy duration was observed also in recent work by Mease et al (23), although they used data of patients enrolled in the CorEvitas RA registry between 2004 and 2015 and studied a smaller set of therapies. There exist some studies that have tried to describe sequential therapies using Sankey diagrams (12,13). Our sequence visualizations contain more information in the sense that they show entire therapy trajectories and not only transitions between consecutive therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Our sequence visualizations contain more information in the sense that they show entire therapy trajectories and not only transitions between consecutive therapies. Still, it is worth noting that Zhao et al (13) identi ed the transition between TNFi and rituximab as the second most common transition between the rst two lines of treatment. In contrast, there are no sequences starting in this way in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients will be offered subsequent b/tsDMARDs on inadequate response to their first but, for some, disease remission remains elusive. A 2022 UK study describing patients who had received up to 10 sequential b/tsDMARDs illustrates this point 106. Although the full definition of the EULAR difficult-to-treat definition is difficult to apply to existing research databases, a UK publication including 13 502 patients starting their first anti-TNF treatment found that 29% went on to receive two different classes of bDMARDs, and 6% received three different classes 107.…”
Section: Difficult To Treat Rheumatoid Arthritismentioning
confidence: 99%